(untitled) (Proceedings of the YSU C: Geological and Geographical Sciences, 2018)
The earlier described "ringing tufas", that were regarded as normal pyroclastic tufas, are explosive breccias of andesite composition, epigenetic with regard to the enclosing strata. The explosive breccias of the Ore Region of Alaverdi generate both embedded interlayer formations and shapless dyke-resembling bodies of the paleogenic age, but not as stratum unit in the column of Oxford.